Slave And Freeman : The Autobiography of George L. Knox - Knox, George L., 1841-1927 (Book collections on Project MUSE., 1979)
Born in Tennessee in 1841, George L. Knox survived slavery and service with both Confederate and Union armies during the Civil War and afterward made his way north to find a chilly reception in Indiana. His autobiography covers the first 44 years of his life and tells how he persevered against threats, harassment, and physical intimidation to become a leading citizen of Indianapolis and an important figure of the Republican Party.